Epidemiological features, echocardiographic findings, and parasite load in patients with Chagas disease - Hilda Maria Benevides da Silva de Arruda; Marcelle Araújo Ribeiro; Antonia Marilene da Silva; Daniel Vasconcelos; Maria Regina Fernandes de Oliveira; Elza Ferreira Noronha (Revista da Sociedade Brasileira de Medicina Tropical, 2019)
Abstract INTRODUCTION Chagas disease is a major public health problem that is endemic in Brazil and Latin America. This study aimed to determine the socioeconomic, demographic, and clinical characteristics of 171 patients (mean age, 45 years; female, 65%) with Chagas disease at Hospital Universitário de Brasília, Federal District, Brazil. METHODS We implemented this cross-sectional study using a clinical epidemiological questionnaire, electrocardiography, echocardiography, and quantitative detection of Trypanosoma cruzi DNA in blood using qRT-PCR. RESULTS Among the patients, 26.3% had a full elementary education, and 13.2% were illiterate. Most (63.6%) were economically classified as class C, and 51.5% were born in Bahia state. A total of 62.0% participants reported previous contact with the triatomine bug. The clinical forms of the disease were indeterminate (69.51%), cardiac (15.24%), digestive (10.37%), and mixed (4.88%). The most common electrocardiographic abnormality was complete right bundle branch block in association with a divisional anterosuperior block. Only 14.6% of the patients complied with benznidazole medication for at least 60 days, and 164 of them were assessed by echocardiography. The parasite load was positive in 56% of the patients. CONCLUSIONS: Chagas disease affected mostly women, with the indeterminate chronic form of the disease.